PENGARUH KOMUNIKASI TERAPEUTIK PETUGAS KESEHATAN TERHADAP KEPUASAN PASIEN RAWAT INAP DI RUMAH SAKIT UMUM HERNA MEDAN - HANDY TARIGAN; MAGDALENA GINTING (JURNAL ILMIAH KOHESI, 2019)
Therapeutic communication is applied by nurses in interacting with patients to increase mutual trust and if not applied will interfere with therapeutic relationships that have an impact on patient dissatisfaction. Patients will feel satisfied when the performance of health services obtained is the same or exceeds expectations and vice versa, dissatisfaction or feeling disappointed by the patient will arise if the performance of the health services obtained is not in line with their expectations. In nursing practice, communication is an important tool to foster teraupetic relationships and can affect the quality of nursing services while therapeutic communication is consciously planned communication, aims, activities focused on patient recovery and is a professional communication carried out by nurses. The purpose of this study was to analyze the effect of therapeutic communication of health workers on the satisfaction of hospitalized patients at Herna Medan General Hospital. This type of research is analytical survey research with cross sectional approach. The population in this study were 326 inpatients at Medan General Herna Hospital. So the sample size in this study amounted to 77 people (simple random sampling). The results showed that the majority of therapeutic communication was not good, patient satisfaction was not satisfied with the influence of therapeutic communication of health workers on the satisfaction of hospitalized patients in Herna Medan General Hospital p. Value 0.000 <0.005. It is expected that health workers improve therapeutic communication and improve services to improve service quality so that patient satisfaction can be optimized